Daya Simpan Probiotik Bakteri Asam Laktat asal Larva Black Soldier Fly Terenkapsulasi: Shelf-life of Encapsulated Lactic Acid Bacteria Probiotics from Black Soldier - Fassah, Dilla Mareistia; Hairani, Atikah; Meryandini, Anja; Astuti, Dewi Apri; Wiryawan, I Komang Gede (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Lactic acid bacteria as probiotic candidates can be isolated from black soldier fly larvae. This study aimed to develop encapsulated lactic acid bacteria (LAB) probiotics from BSF larvae and to evaluate the effect of encapsulation on probiotic viability during 12 weeks of storage at room temperature and 4°C. The experimental design was a factorial completely randomized design with two treatments: storage temperature and storagetime. The variables observed are the number of cells and the level of cell resistance. The result showed that based on the growth curve of LAB isolates from BSF larvae, they could be harvested at 16 hours of age to be produced as probiotics. Encapsulated LAB probiotics from BSF larvae had a population of lactic acid bacteri (LAB) 107 CFU g-1 and were able to maintain the cell viability of 99.3%. Temperature and storage timesignificantly affect (p<0.05) the viability of encapsulated LAB. It can be conclude that encapsulation was able to optimally maintain the LAB viability at temperature of 4°C for 4 weeks of storage. Key words: black soldier fly larvae, encapsulation, probiotic, storability, viability